2008
DOI: 10.2137/145960607784125375
|View full text |Cite
|
Sign up to set email alerts
|

Reduced fertiliser use and changes in cereal grain weight, test weight and protein content in Finland in 1990-2005

Abstract: Since 1995 the Finnish Agri-Environmental Program has set limits for nitrogen (N) and phosphorus (P) fertiliser application rates in agriculture. The decrease in N and P fertiliser recommendations, and especially the decrase in N and P amounts applied in practice, has raised the question of whether N and P application rates are too low to produce high quality yields. The test weight, 1000 grain weight and protein concentrations measured in 1990-2005 by the Cereal Inspection Unit of the Finnish Food Safety Auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Annual variation in N content of grains can also introduce error into the balances. Results from an annual survey of the Finnish Food Safety Authority (Salo et al 2007) suggested that variation of N content in cereals was 0.3-0.5 percentage points over years and regions. Regional calculations could be improved by using these data.…”
Section: Uncertainty In N Balance Calculationsmentioning
confidence: 99%
“…Annual variation in N content of grains can also introduce error into the balances. Results from an annual survey of the Finnish Food Safety Authority (Salo et al 2007) suggested that variation of N content in cereals was 0.3-0.5 percentage points over years and regions. Regional calculations could be improved by using these data.…”
Section: Uncertainty In N Balance Calculationsmentioning
confidence: 99%
“…According to earlier reports, it was found that P fertilization has a negligible effect on the protein content, but may affect the 1,000-seed weight and the test weight (e.g. Saarela et al 1995;Salo et al 2007).…”
Section: Introductionmentioning
confidence: 97%
“…Data based on Finnish farm surveys showed that, in 1990-2005, reduced N application rates were associated with lower test weight and 1000 grain weight (Salo et al 2007b). However, the magnitude of grain quality reduction was not solely explicable by N application rates, since many other factors and management practices changed in Finnish cereal production during that period.…”
Section: Discussionmentioning
confidence: 99%